How digital skills affect farmers' agricultural entrepreneurship? An explanation from factor availability - Changming Cheng; Qiang Gao; Kexin Ju; Yuting Ma (Journal of Innovation & Knowledge (JIK), 2024)
Promoting rural household agricultural entrepreneurship is a key way to increase farmers' income and achieve rural revitalization. In the growing digital economy, the ability to use the internet to access information is crucial for agricultural entrepreneurship. Based on the data of China Land Economic Survey, this paper uses the panel Logit fixed-effects model to investigate the impact of digital skills on farmers' agricultural entrepreneurship and the underlying mechanisms. The findings indicate that digital skills have a statistically significant positive influence on farmers' agricultural entrepreneurship. Furthermore, digital skills can enhance farmers' agricultural entrepreneurship by increasing factor availability, including production credit, modern technology, and social capital. The positive effect of digital skills on farmers' agricultural entrepreneurship is more pronounced for farmer groups with more farming experience, greater land resources, no major adversities experienced and lack optimistic expectations for the future. Additionally, this research revealed differences in the impact of different types of digital skills on farmers' agricultural and non-agricultural entrepreneurship. This study contributes to the micro analysis from the perspective of farmers' agricultural entrepreneurship, which provides policy implications for developing countries worldwide to enhance agricultural entrepreneurship by improving digital skills.
Keywords: L26; J23; P25; 650; Agricultural entrepreneurship; Digital skills; Modern technology availability; Production credit availability; Social capital availability